The Paradox of Southern Cameroons’ Economic Viability Debate in Colonial Lenses: A Post-Colonial Critique of the British Underdevelopment Tactics, 1922-2022 - Elvis Nkome Ngome (PanAfrican Journal of Governance and Development)
The idea of developing and granting political independence to the British colonial sphere of Southern Cameroons depended greatly on the country’s economic potential. Although the territory inherited several German structures like colonial plantations and buildings, the British were not convinced that the territory would be economically viable and sustain itself if it were granted independence as an autonomous state. In order to exonerate the colonial government from future decisive political decisions for the future of the country, the interim southern Cameroons government, acting under the aegis of the British colonial authorities, requested for studies to be conducted on the 'economic' viability of the British colony of Southern Cameroons in the 1950s. The results of the studies were damaging, and their conclusion showed an economic ‘red card’ to politicians who aspired for an independent Southern Cameroons. The hypothesis of economic unviability of the Southern Cameroons appears interesting, but unfortunately, very little research has been done by Cameroonian scholars to debunk colonial assertions of unviability. The paper attempts to investigate the so-called economic viability debate in the history of Southern Cameroons using decolonial interpretations to unpack the colonial assertions. The study adopted the interdisciplinary methodology to exploit primary and secondary data. Primary data was obtained from the National Archives in Buea, while a desk review of secondary sources was done at the University of Buea library in Cameroon. The sources reviewed enabled the researcher to obtain verifiable data capable of providing evidence against the negative colonial reports on the economic viability of the former British Southern Cameroons. The data obtained was critically analyzed from a decolonial perspective and presented qualitatively.